Obstetric Provider Approach to Perinatal Oral Health [120]. (May 2015) - Wilson, Eline Haenebalcke; Farrell, Chris; Zielinski, Ruth Elaine; Gonik, Bernard
Abstract : INTRODUCTION: Perinatal oral health is a critical component to obstetric practice with significant implications for maternal, fetal, and infant health. To better understand this relationship, we undertook a survey of obstetric providers to examine their approach to perinatal oral health. METHODS: An online survey of knowledge, attitudes, and practices was sent using health care provider databases in the state of Michigan. Descriptive statistics were tabulated and Fisher's exact test was used for categorical variables. RESULTS: There were a total of 146 respondents, 80 obstetrician–gynecologists and 66 certified nurse midwife providers. Eighty-five percent of providers (117/137) acknowledged that perinatal oral health is an important consideration for optimal prenatal care, whereas only 53% (78/146) reported having questions specific to oral health on their intake documents. During prenatal care, 36% (51/140) regularly discuss oral health, 30% (42/140) routinely perform an oral cavity examination, and 44% (61/138) consistently recommend oral health assessment by a dentist. Certified nurse midwife providers were more likely than obstetrics and gynecology providers to routinely discuss the importance of oral health in prenatal care, 50% compared with 24%, respectively ( P <.05). CONCLUSION: These findings demonstrate a dichotomy of care in that obstetric providers recognize the importance of oral health care in pregnancy, but only a minority routinely incorporates these practices. These data highlight a significant gap in obstetric services that needs attention through specific educational initiatives and further research endeavors that address health care provider, practice, and patient barriers.